Fiber Yield, Physical and Biochemical Properties of Three Species of Sesbania - Chanda, SC; Hossain, MS; Uddin, MM; Islam, MM; Sarwar, AKM Golam (Bangladesh Agronomy Journal, 2019)
An experiment was conducted at Field Laboratory of the Department of Crop Botany, Bangladesh Agricultural University, Mymensingh to compare the fiber yield, physical and biochemical properties of three Sesbania species. A total of 38 accessions, 28 from S. bispinosa, 4 from S. cannabina and 5 from S. sesban were used as experimental materials. Seeds were sown @ 30 kg ha-1 on 23 April, 2016 following randomized complete block design with three replications. Each plot size was 4.0×2.5 m2 maintaining at the spacing of 50 cm row to row and 15 cm plant to plant. Plants were harvested at 120 days after sowing and plant height, base diameter, plant fresh weight and dry fiber as well as dry stick weight were measured. The fiber yield was the highest in S. bispinosa (2.18 g plant-1) and the lowest in S. sesban (1.40 g plant-1). Fiber luster (%), strength (g tex-1) and crude fiber (%) showed significant differences among these three species. Both fiber luster and strength showed the highest value in S. cannabina (53.50% and 51.20 g tex-1, respectively) and the lowest in S. sesban (35.16% and 33.68 g tex-1). Crude fiber (%) was also the maximum in S. cannabina (41.41%) and the minimum in S. sesban (25.57%). It may, therefore, be concluded that fiber quality of S. cannabina was superior to other species and could be possible to blend with other natural fiber for industrial purposes. Bangladesh Agron. J. 2018, 21(2): 79-85